Moderating effect of coworker support on the relationship between HRM practices, organizational climate, leadership styles and organizational commitment - Ahmad, Ashfaq (2016)
This study was conducted among the academic staff in public higher education sector in Khyber Pakhtunkhwa (KPK), Pakistan. The main objective of the study was to determine the effect of human resource management practices, organizational climate, and leadership styles on organizational commitment. A total of 354 academic staff from universities located in the KPK, Pakistan participated in the study. The results revealed statistically significant support for the relationship between training and development and organizational commitment; compensation and organizational commitment; organizational climate and organizational commitment; transformational leadership style and organizational commitment; transactional leadership style and organizational commitment. However, no statistically significant support was found for the relationship between performance appraisal and organizational commitment. Moreover, the results reported moderating effect of coworker support over the relationship between compensation and organizational commitment; organizational climate and organizational commitment; transformational leadership style and organizational commitment; and transactional leadership style and organizational commitment. On the contrary, the results could not find support for the moderating effect of coworker support on the relationship between training and development and organizational commitment; and between performance appraisal and organizational commitment. In general, the empirical relationships between HRM practices, organizational climate, leadership style, coworker support, and organizational commitment suggested that it would be beneficial to the management of public sector universities to enhance organizational commitment. Besides that, theoretical and practical implications are also discussed.